(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: People suffering from epilepsy requires a long period of treatment and regular monitoring. Extensive use of antiepileptic drugs warrants critical monitoring to suggest appropriate clinical use and safety considerations. Objectives: The study was aimed to analyse the prescription pattern of antiepileptic drugs in a tertiary care hospital in Kanchipuram. Methodology: This was a prospective, observational study conducted in outpatient departments at Meenakshi medical college Hospital and Research institute. Institutionalethical clearance was obtained. Results: Monotherapy were prescribed among 69.9% of patients and 30.08% of patients received polytherapy. levetiracetam (23.8%) was the most prescribed drug followed by benzodiazepines (16.8%), hydantoin drugs such as phenytoin, fosphenytoin (11.5%), valproic acid(10.6%) and iminostilbenes such as carbamazepine and oxcarbazepine(5.3%).AEDs were more prescribed only for seizure disorder (79%) than any other disease conditions. Conclusion: A shift from the use of conventional antiepileptic drugs to the newer AED’s was observed, which dominated the pharmacotherapy of epileptic seizures. This would form a part of pharmacoepidemiology and will update the treatment guidelines benefitting the physicians regarding optimal use of antiepileptic drugs